Susceptibility of metallic magnesium implants to bacterial biofilm infections. Issue 6 (24th February 2016) - Rahim, Muhammad Imran; Rohde, Manfred; Rais, Bushra; Seitz, Jan‐Marten; Mueller, Peter P.
Abstract: Magnesium alloys have promising mechanical and biological properties as biodegradable medical implant materials for temporary applications during bone healing or as vascular stents. Whereas conventional implants are prone to colonization by treatment resistant microbial biofilms in which bacteria are embedded in a protective matrix, magnesium alloys have been reported to act antibacterial in vitro . To permit a basic assessment of antibacterial properties of implant materials in vivo an economic but robust animal model was established. Subcutaneous magnesium implants were inoculated with bacteria in a mouse model. Contrary to the expectations, bacterial activity was enhanced and prolonged in the presence of magnesium implants. Systemic antibiotic treatments were remarkably ineffective, which is a typical property of bacterial biofilms. Biofilm formation was further supported by electron microscopic analyses that revealed highly dense bacterial populations and evidence for the presence of extracellular matrix material. Bacterial agglomerates could be detected not only on the implant surface but also at a limited distance in the peri‐implant tissue. Therefore, precautions may be necessary to minimize risks of metallic magnesium‐containing implants in prospective clinical applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1489–1499, 2016.